2019
DOI: 10.1002/jgc4.1123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling, 2030: An on‐demand service tailored to the needs of a price conscious, genetically literate, and busy world

Abstract: The practice of genetic counseling is going to be impacted by the public's expectation that goods, services, information, and experiences happen on demand, wherever and whenever people want them. Building from trends that are currently taking shape, this article looks just over a decade into the future—to 2030—to provide a description of how the field of genetics and genetic counseling will be changed, as well as advice for genetic counselors for how to prepare. We build from the prediction that a large portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…In one other use of a conversational agent for a related application in the context of chronic conditions (eg, cardiovascular disease, diabetes, and cancer), Wang et al [ 39 ] developed an animated virtual counselor to collect electronic family health histories for clinical risk assessment [ 29 , 30 ] and as a proxy for genetic predisposition to personalize medical care and disease prevention [ 40 - 45 ]. In a randomized comparison with the Surgeon General’s My Family Health Portrait [ 46 ], the conversational agent had better acceptability and usability outcomes (eg, ease of use, flow, understanding information, and satisfaction).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one other use of a conversational agent for a related application in the context of chronic conditions (eg, cardiovascular disease, diabetes, and cancer), Wang et al [ 39 ] developed an animated virtual counselor to collect electronic family health histories for clinical risk assessment [ 29 , 30 ] and as a proxy for genetic predisposition to personalize medical care and disease prevention [ 40 - 45 ]. In a randomized comparison with the Surgeon General’s My Family Health Portrait [ 46 ], the conversational agent had better acceptability and usability outcomes (eg, ease of use, flow, understanding information, and satisfaction).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently have clinical cancer care settings begun to leverage this technology to support patient information management in service delivery [ 4 ]. Conversational agents have been used in some of these processes, such as collecting patient data, providing genetic information, delivering results, and facilitating cascade testing of at-risk relatives in clinical settings [ 18 , 27 - 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is likely to become increasingly important in the future as the development and use of electronic decision aids and artificial intelligence (e.g., chatbots) in clinical genetics services moves forward. [178][179][180] Many studies highlighted the potential of alternative service delivery models, but while a recent systematic review of randomized controlled trials of outcomes of genetic counseling found that these can be as effective as in-person counseling in some settings (e.g., women at risk for hereditary cancer), 181 it is important to emphasize that there remains a subset of patients for whom appropriate genetic counseling and testing will require the traditional in-person two-appointment model. Care needs to be taken when implementing efficiency improvement initiatives to ensure that appropriate services are available for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Primary care providers have indicated unease with interpreting results (Hauser, Obeng, Fei, Ramos, & Horowitz, 2018) and counseling patients (Evenson, Hoyme, Haugen‐Rogers, Larson, & Puumala, 2016). These providers often rely on the expertise of genetic counselors; however, the demand for genetic counselors exceeds the current supply, and nonspecialists are not always aware of when to refer a patient to a specialist (Rashkin et al, 2019; Selkirk, Weissman, Anderson, & Hulick, 2013; Vassy et al, 2017). Similarly, a recent survey among primary care providers on their attitudes toward pharmacogenomic testing showed that 76% believed this type of testing can improve care; however, only 26% reported confidence in using such testing in prescribing decisions, and 70% preferred a pharmacist consultation (Smith et al, 2020).…”
Section: Translating Genomics To Routine Clinical Practice: Challengesmentioning
confidence: 99%